SAS macro programme for Bang’s Blinding Index to assess and visualise the success of blinding in randomised controlled trials - Hongqiu Gu; Zhen Wang; Yangfeng Wu; Jiani Wu; Zongshi Qin; Toshiaki Furukawa; Yongpei Yu; Dongdong Shi (General Psychiatry)
This paper aims to present a Statistical Analysis Software (SAS) macro %BBIplus, offering estimation and visualisation methods for the Bang’s Blinding Index (BBI) for randomised controlled trials (RCTs) with various designs. We developed the SAS macro programme %BBIplus to facilitate the implementation of BBI. This user-friendly programme allows for easy and rapid estimation and visualisation of BBI across different scenarios, including pairwise comparison RCTs with two arms, double-dummy design RCTs with three arms and factorial design RCTs with four arms. The programme requires no pre-existing data set, and users only need to input the number of individuals of correct, uncertain or wrong guesses in each intervention or control group. We illustrate the functionality of %BBIplus using blinding assessment data from three previously published RCTs: BBR (adjunctive berberine reduces antipsychotic-associated weight gain and metabolic syndrome in patients with schizophrenia: a randomised controlled trial), SELECT-TDCS (the sertraline versus electrical current therapy for treating depression clinical study: results from a factorial, randomised controlled trial) and ELECT-TDCS (trial of electrical direct-current therapy versus escitalopram for depression) studies. The programme estimates the BBI for each arm, providing point estimates, 95% CI and associated p values. Additionally, %BBIplus can visualise the estimations through forest plots and make the judgement for the success of blinding easily and rapidly. This tool caters to the needs of clinical trial investigators, offering a comprehensive solution for estimating and visualising the blinding index under various RCT designs.